Beyond Socio-Historical Trauma with Olga Zhukova and Iskra Babich: Re-Reading Cinema of Perestroika - Natasha Poglajen (GoAcademica Research & Publishing, 2019)
Cinematography of perestroika (and the early post-Soviet period) entails mixed terra-in, often described as a socially-critical “black wave” chernukha; the period saw an unprecedented number of works by female directors, which remain to be addressed by film scholarship. This article examines the cinematic opus of Olga Zhukova (1954-) who produced five feature films in the period 1990–1994. This article discusses her films, which were not well received by critics and accused of being pretentious and artificial, alongside another Soviet director, Iskra Babich (1938–2001). I re-examine the formation of Zhukova’s cinematic speech, focusing on the interplay of the audio-visual and corporeal, to argue that her works create specific times paces which defy the immediate socio-political references provided by the seemingly formative linear narratives, and bypass the patriarchal dichotomies underpinning the latter.